Assessment of land degradation in semi-arid Tanzania: Using remote sensing to inform the Sustainable Development Goal 15.3 - Reith, J.A. (University of Bonn, 2020)
Monitoring land degradation (LD) to inform the sustainable development goal (SDG) 15.3.1 (\proportion of land that is degraded over total land area") is key to ensure a more sustainable future. At the moment, there are only default medium-resolution datasets available to assess LD in Tanzania. They do not reflect local characteristics and cannot help to target exposed areas spatially.